Real Big Data: How We Know Who We Know in Youth Work. Issue 2 (3rd April 2021) - Fink, Alexander; Brito, Marisol
Abstract: As the generation and use of big data becomes more prevalent in youth work, young people grow up in a world that "knows" more about their lives than ever before. Beyond school attendance and grades, these systems know about out-of-school program participation, social service resources, therapeutic interventions, and more. Though data historically was used to understand and improve program achievements, communicate with funders, and track participants, it is increasingly used to suggest and even perform interventions in young peoples' lives. Young people are rarely asked how they feel about these systems. This study, presented as a counter-narrative from their perspective, differentiates the big data collected and analyzed about them from the "big data" - or stuff that they feel really matters about who they are and the challenges they face. It concludes by offering four questions to help youth-serving organizations consider the ways they generate and use data, in light of the many issues young people raise about new big data trends.